Longitudinal Neuropsychological Outcome in Taiwanese Alzheimer's Disease Patients Treated with Medication - Yang, Yuan-Han; Wu, Meng-Ni; Chou, Ping-Song; Su, Hui-Chen; Lin, Sheng-Hsiang; Sung, Pi-Shan (Current Alzheimer Research, 2018)
Background: The longitudinal change of neuropsychological tests (NPTs) in treated Alzheimer's disease (AD) is essential to understand the interplay of a therapeutic response from medication and a disease decline due to degenerative processes. The aim of our study is to investigate the annual cognitive progression as measured by commonly used NPTs in treated AD patients and to assess the potential predictors of disease progression. Methods: Participants (N=455) diagnosed with AD and treated with cholinesterase inhibitors (ChEIs) or memantine at memory clinics in three hospitals in southern Taiwan from January 2009 to December 2014 were enrolled in this prospectively registered study. The mean follow-up duration was 3.2 ± 0.9 years. The patients' severity of AD ranged from very mild (clinical dementia rating (CDR) scales = 0.5) to moderate (CDR = 2.0). At baseline and for each year, participants were assessed by various NPTs commonly used in clinical practice, including the Mini-Mental State Examination (MMSE), Cognitive Abilities Screening Instrument (CASI), CDR and CDR-sum of boxes (CDR-SB). All enrolled participants were assessed for at least two years during follow-up. We used mixed-effect models to examine annual progression in the whole group and to compare the cognitive progression between the subgroups with very mild AD and mild to moderate AD. Potential predictors of disease progression, including age, gender, the type of ChEI, and Apolipoprotein E (APOE) genotype, were also analyzed. Results: Among the study population, the rate of change in MMSE scores were -1.15 points per year, CASI scores were -4.27 points per year, and CDR-SB scores were 0.81 points per year. The slope of annual changes of NPTs differed significantly between the CDR 0.5 group and the CDR 1 to 2 group. The most significant predictors of the faster progression were increasing age and higher CDR stage at entry; however, different types of ChEI therapy (donepezil vs. rivastigmine users), and APOE genotype were not associated with the rate of disease progression. Conclusions: This longitudinal data shows the mean annual change of the MMSE, CASI, CDR, and CDR-SB in treated AD patients. The data may provide clinicians with information regarding to the cognitive decline rate in every year while their AD patients receive approved pharmacological therapy in real-world practice. Increasing age and severity of dementia when receiving therapy are the main factors that associated with faster deterioration.
Keywords: serial cognitive assessment